The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11356-020-09733-w
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concern regarding the effect of humidity and temperature on 2019-nCoV survival: fact or fiction

Abstract: The new coronavirus, called 2019-nCoV, is a new type of virus that was first identified in Wuhan, China, in December 2019. Environmental conditions necessary for survival and spread of 2019-nCoV are somewhat transparent but unlike animal coronaviruses. We are poorly aware of their survival in environment and precise factors of their transmission. Countries located in east and west of globe did not have a significant impact on prevalence of disease among communities, and on the other hand, north and south have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 81 publications
3
46
0
Order By: Relevance
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and COVID-19 transmissibility. [23][24][25][26][27] Our results also are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility. 23,27 The study duration mark a period of increasing temperature in the Indian peninsula and our results indicate that, in general, high ambient temperatures were associated with lower R 0 estimates such that unit standard deviation increase in air temperature was associated with a 0.08 lower R 0 (Table 1, final model).On the other hand, we observed that a unit standard deviation increase in wind speed was associated with a 0.08 higher R 0 ( Table 1, (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 90%
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and COVID-19 transmissibility. [23][24][25][26][27] Our results also are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility. 23,27 The study duration mark a period of increasing temperature in the Indian peninsula and our results indicate that, in general, high ambient temperatures were associated with lower R 0 estimates such that unit standard deviation increase in air temperature was associated with a 0.08 lower R 0 (Table 1, final model).On the other hand, we observed that a unit standard deviation increase in wind speed was associated with a 0.08 higher R 0 ( Table 1, (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 90%
“…Middle East respiratory syndrome-related coronavirus cases have also shown an increase with high temperatures, coupled with high ultraviolet index, low wind speeds, and low relative humidity (Altamimi et al 2019). Harmooshi et al ( 2020 ) have observed that the COVID-19 can survive for up to 9 days at 25 °C, and if this temperature rises to 30 °C, its lifespan will be shorter. Likewise, the COVID-19 is sensitive to humidity, and lifespan of viruses in 50% humidity is longer than that of 30%.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers around the world have demonstrated an inverse relationship between air temperature and number of COVID-19 cases ( Demongeot et al, 2020 ; Guo et al, 2020 ; Harmooshi et al, 2020 ; Jahangiri et al, 2020 ; Malki et al, 2020 ; Pramanik et al, 2020 ; Ran et al, 2020 ; Ren et al, 2020 ; Seligmann et al, 2020a ; Steiger et al, 2020 ). Our results are in agreement with the general understanding that higher ambient temperature can inversely influence COVID-19 transmissibility ( Guo et al, 2020 ; Jahangiri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%